A Koli lady carrying a container of holy water - Mumbai Archive Project Team (Jio Institute, 2024)
A Koli lady carrying a container of holy water moves ahead of the procession and sprinkles water on the path using a genda phool (marigold flower). This practice symbolizes the purification, sanctification, and blessing of the path to ensure the smooth and auspicious progress of the procession.